Stages of the formation of accounting science and its further development - Pushkar, Mykhailo; Semaniuk, Vita (Herald of Economics, 2023)
Introduction. The article presents a research study on the stages of the formation of accounting science under the influence of economic, social, technological, psychological, and other factors. This research has allowed investigating the essence of accounting and its impact on the evolution of humanity’s economic activities. The examination of historical aspects has enabled the formulation of predictions regarding the development of accounting paradigms in the future. It has been proven that accounting theory requires improvement and an enhancement of its scientific rigor.Research objective. The objective of the study is to explore the stages of formation of accounting science and to forecast the future development of accounting concepts in the context of significant transformation of the business information environment and the advancement of information technologies.Research methods. The stages of the formation of accounting science were studied using the bibliographic method, specifically through the implementation of monographic and comparative analysis of accounting theory, methods of forming information resources for business, and critical analysis of historical theories of societal development. The methods of theoretical modeling and scientific abstraction were employed to forecast the future development prospects of accounting concepts.Results. The historical aspects of accounting science formation were examined in the context of the transformation of scientific theory. The stages of accounting science formation were identified, highlighting the accounting system as one that meets the requirements of an industrial-type economy, necessitating a fundamental revision of accounting theory. It was demonstrated that in a technologically and informationally advanced world, information resources should form the core of the accounting system as a product of its functioning. The study also established that economic activity is a fundamental element of contemporary accounting science. The article proposes an author’s vision of the stages of accounting paradigm formation and the directions for the development of accounting science and the theory of accounting in a post-industrial digital society. The implementation of the proposed measures will elevate accounting science to a higher level of development and interpret accounting as a process of creating information and shaping the information field of business at various levels of management. It will also provide an understanding of the impact of information resources on the process of managerial decision-making.Prospects. Further scientific research should focus on studying the problems of accounting theory formation in accordance with the needs of scientific and economic progress, as well as forecasting the transformation of accounting theory and methodology considering the impact of economic digitization.